Clinical diagnosis of Alzheimer's disease: Recommendations of the International Working Group (IWG). (31st December 2021) - Villain, Nicolas; Dubois, Bruno; Frisoni, Giovanni B.; Rabinovici, Gil D.; Sabbagh, Marwan Noel; Cappa, Stefano; Bejanin, Alexandre; Bombois, Stéphanie; Epelbaum, Stéphane; Teichmann, Marc; Habert, Marie‐Odile; Nordberg, Agneta K.; et al.
Abstract: Background: In 2018, the National Institute of Aging and the Alzheimer Association proposed a purely biological definition of Alzheimer's disease (AD) relying on biomarkers. While the intended use of the framework was for research purposes, it has engendered debate and challenges regarding its application in everyday clinical practice. For instance, cognitively unimpaired individuals may have biomarker evidence of both amyloid and tau pathology, but may never develop clinical manifestations in their lifetime. Furthermore, a positive AD pattern may be observed in other brain diseases where AD pathology is present as co‐pathology. In this presentation, the international Working Group (IWG) presents what we consider to be the current limitations of biomarkers in the diagnosis of AD, and on the basis of this evidence we propose recommendations for how biomarkers should and should not be used for diagnosis of AD in a clinical setting. We recommend that AD diagnosis be restricted to the occurrence of positive biomarkers together with specific AD phenotypes, whereas biomarker positive cognitively unimpaired individuals should be considered only at‐risk for progression to AD.